Influence of oats and oat products in phase I and II diets on growth performance of weanling pigs - M M Rantanen; M R Cabrera; L L Burnham; Robert H Hines; Joe D Hancock (Kansas Agricultural Experiment Station Research Reports, 1994)
Two experiments were conducted to determine the nutritional value of oats and oat products in diets of weanling pigs. In Exp. 1, 115 weanling pigs (avg initial body wt of 12.4 lb and avg age of 19 d) were used in a 38-d growth assay. Treatments were 1) a corn-soybean meal-based control, 2) ground oats, 3) oat groats, and 4) oat flour. Phase I diets were formulated to 1.55% lysine, and at d 10 postweaning the pigs were switched to a Phase II diets formulated to 1.3% lysine. At d 24 postweaning, all pigs were changed to a sorghum-based Phase III diet. The diets were fed in pelleted form. For Phase I, pigs fed the oat products tended to have greater efficiencies of gain compared to pigs fed corn. Pigs fed the reduced fiber oat products (groats and flour) were more efficient than pigs fed ground whole oats, and the most refined oat product (oat flour) tended to support the greatest efficiencies of gain (8% greater ADG and 13% greater F/G than the corn control). These same trends for pigs fed oat flour were noted in Phase II and for the overall experiment (I.e., d 0 to 38). In Exp. 2, 172 weanling pigs (avg initial body wt of 12.5 lb and avg age of 19 d) were used in a second 38-d growth assay. Treatments were 1) a com-soybean meal-based control, 2) ground oats, 3) roasted oats, 4) oat groats, 5) steam-flaked oat groats, and 6) oat flour. The data indicated that roasting decreased the nutritional value of ground oats. However, steam-flaking improved the nutritional value of oat groats. Feeding diets formulated with processed oat products (i.e., steam-flaked oat groats and oat flour) improved F/G through Phase II (e.g., 6% greater efficiency of gain compared to the corn-based control), but much of that advantage was lost during Phase III while the pigs were fed the same sorghum- based diet. In conclusion, the most refined oat products (steam-flaked oat groats and oat flour) supported better F/G than com in Phases I and II. However, cost must be continuously balanced against the improved performance to ensure that use of these oat products is economically viable.; Swine Day, Manhattan, KS, November 17, 1994
Keywords: Swine day; 1994; Kansas Agricultural Experiment Station contribution; no. 95-175-S; Report of progress (Kansas State University. Agricultural Experiment Station and Cooperative Extension Service); 717; Swine; Pigs; Carbohydrate; Starter; Oat; Growth